Kisspeptin is providing new insights into the control of reproduction - Izzi-Engbeaya, Chioma (Clin Med (Lond), 2013)
The kisspeptins are a group of recently discovered peptide hormones (collectively termed kisspeptin), which play a pivotal role in reproduction. Research investigating the actions of kisspeptin is helping to elucidate the regulatory mechanisms which govern fertility and may lead to the development of novel treatments for some reproductive disorders.